Gut inflammation in spondyloarthritis. Issue 6 (December 2017) - Rizzo, Aroldo; Ferrante, Angelo; Guggino, Giuliana; Ciccia, Francesco
Abstract: Spondyloarthritis (SpA) is a group of related diseases sharing common etiopathogenic mechanisms and clinical manifestations supported by a complex genetic predisposition. Gut inflammation is present in patients with SpA including patients showing clinically evident intestinal inflammation in the form of Crohn's disease or ulcerative colitis and patients who despite the absence of signs and symptoms of intestinal inflammation display a subclinical gut inflammation. Emerging evidence suggests that subclinical gut inflammation in patients with SpA, apparently driven by intestinal dysbiosis, is not the consequence of the systemic inflammatory process but rather an important pathophysiological event actively participating in the pathogenesis of the disease. The dysregulation of intestinal epithelial barrier possibly modulated by intestinal dysbiosis and especially in HLA-B27 + patients modulates local and systemic inflammation possibly representing the occult mechanism of the disease. This review aims to summarise current data on the role of the gastrointestinal involvement and intestinal microbiota in the pathogenesis of systemic rheumatic disease.